TEMPORARY ANCHORAGE DEVICE - IS IT THE ULTIMATE ANCHORAGE SYSTEM IN ORTHODONTICS? - A REVIEW. - MS NARMADHA SUDHAKAR; DR.SARAVANADINESH.S.P (International Journal of Pharma and Bio Sciences, 2014)
Anchorage control is one of the main aspects of orthodontic treatment plan. Mini-screw implants, often referred to as temporary anchorage devices, have become an accepted component of orthodontic treatment. A temporary anchorage device is defined as that device which aids in augmenting orthodontic anchorage, it sometimes even eliminates the need of anchor teeth. It is temporarily inserted into bone and can be subsequently removed after use. By using temporary anchorage devices for orthodontic purposes we are able to obtain zero anchorage loss.